Re-imagining Marketing Scholarship in the era of the UN Sustainable Development Goals. Issue 2 (May 2022) - Voola, Ranjit; Carlson, Jamie; Azmat, Fara; Viet Ngo, Liem; Porter, Kylie; Sinha, Ashish
The pandemic, rising inequalities, climate change, consumer mistrust of brands, organizations and their intentions, pose important questions relating to marketing's relevance and impact in the real world. Additionally, there are growing calls by global bodies, such as the UN, national governments, consumers, students, suppliers, and leading practitioners to re-imagine and broaden the role of business and marketing to consider benefits to stakeholders (consumers, suppliers, employees, community, as well as shareholders). In this editorial, we contend that the United Nations Sustainable Development Goals (UN SDGs) framework has the potential to address the myriad of challenges identified by marketing scholars and practitioners. With the assistance of quotes from marketing scholars, non-marketing scholars, marketing students and practitioners, we offer a rationale for a proactive and considered engagement by marketing scholarship, with the UN SDGs. We then introduce the six papers included in this special issue. We conclude by calling for further critical inquiry at the marketing-SDGs interface including; 1) Re-imagining the philosophy of marketing and marketing education; 2) Marketing capabilities and the SDGs; 3) Understanding consumer behavior, and 4) Learning across contexts.